A collection of comprehensive cases: Financial Accounting and reporting (I, II & III) - Abu Bakar, Fathiyyah; Abdul Latif, Rohaida; Abdullah, Zaimah; Shaari, Hasnah (UUM Press, 2017)
A Collection of Comprehensive Cases is a compilation book of comprehensive cases for Financial Accounting and Reporting (FAR) I, II and III. This book is specially designed for accounting students in FAR subjects to be more familiar with the format and the structure of comprehensive cases. The objective of this book is to assist students to have a better understanding on the case instructions as well as to guide them on how to answer well those instructions. The book is also meant as a good reference for students as they have their own collection of comprehensive cases and the key answers were also systematically arranged for them to do revision.